Charting a Course for Decarbonizing Maritime Transport : Summary for Policymakers and Industry - Englert, Dominik; Losos, Andrew (World Bank, Washington, DC, 2021)
As the backbone of global trade, international maritime transport connects the world and facilitates economic growth and development, especially in developing countries. However, producing around three percent of global greenhouse gas (GHG) emissions and emitting around 15 percent of some of the world’s major air pollutants, shipping is a major contributor to climate change and air pollution. To mitigate its negative environmental impact, shipping needs to abandon fossil-based bunker fuels and turn to zero-carbon alternatives. This report, the “Summary for Policymakers and Industry,” summarizes recent World Bank research on decarbonizing the maritime sector. The analysis identifies green ammonia and hydrogen as the most promising zero-carbon bunker fuels within the maritime industry at present. These fuels strike the most advantageous balance of favorable features relating to their lifecycle GHG emissions, broader environmental factors, scalability, economics, and technical and safety implications. The analysis also identifies that LNG will likely only play a limited role in shipping’s energy transition due to concerns over methane slip and stranded assets. Crucially, the research reveals that decarbonizing maritime transport offers unique business and development opportunities for developing countries. Developing countries with large renewable energy resources could take advantage of the new and emerging future zero-carbon bunker fuel market, estimated at over $1 trillion, to establish new export markets while also modernizing their own domestic energy and industrial infrastructure. However, strategic policy interventions are needed to hasten the sector’s energy transition.